Internationalisation – dispelling the myth of African inferiority - Mthiyane, Ncamisile P.; Jarvis, Janet (Critical Studies in Teaching and Learning, 2024)
Decoloniality is a framework addressing global power imbalances, particularly between the global north and south, rooted in the process of othering. This article suggests that internationalisation can promote decolonisation, particularly in South Africa, by challenging the notion of inferiority in the global south. Crossing disciplinary and geographical boundaries plays a crucial role in evolving classroom practice into reflective and reflexive classroom praxis. The use of empathetic-reflective-dialogical restorying as a teaching strategy aligns with a decolonial agenda. This approach allows pre-service teachers from diverse geographical contexts, like South Africa and Norway, to engage in empathetic and reflective dialogue within a safe space, potentially reshaping their prior conceptions of best teaching practices. This transformative process holds promise for the classroom environment.